Redefining Teacher-Student Interaction in the Digital Era: A Case Study of Hybrid Learning Models in Primary Education - Puspitasari, Erika (GoAcademica Research & Publishing, 2024)
This study aims to explore the dynamics of teacher-student interactions in the context of hybrid learning in elementary schools. Data were collected through classroom observations, interviews with teachers, and analysis of digital platforms used through a case study approach. Findings indicate that although digital technology provides flexibility in time and space and a variety of interactive tools, student engagement in online sessions tends to be low. Non-verbal communication is also limited, affecting the quality of interpersonal interactions. Digital literacy is key; teachers who can utilize technology well can improve student interaction and engagement, and the challenge of unequal access to technology widens the gap in learning. The implications of this study emphasize the need to improve digital literacy for teachers and students, as well as solutions to overcome technological barriers to support effective hybrid learning in the future.